The contrasting nature of woody plant species in different neotropical forest biomes reflects differences in ecological stability. Issue 1 (11th November 2015) - Pennington, R. Toby; Lavin, Matt
Summary: A fundamental premise of this review is that distinctive phylogenetic and biogeographic patterns in clades endemic to different major biomes illuminate the evolutionary process. In seasonally dry tropical forests (SDTFs), phylogenies are geographically structured and multiple individuals representing single species coalesce. This pattern of monophyletic species, coupled with their old species stem ages, is indicative of maintenance of small effective population sizes over evolutionary timescales, which suggests that SDTF is difficult to immigrate into because of persistent resident lineages adapted to a stable, seasonally dry ecology. By contrast, lack of coalescence in conspecific accessions of abundant and often widespread species is more frequent in rain forests and is likely to reflect large effective population sizes maintained over huge areas by effective seed and pollen flow. Species nonmonophyly, young species stem ages and lack of geographical structure in rain forest phylogenies may reflect more widespread disturbance by drought and landscape evolution causing resident mortality that opens up greater opportunities for immigration and speciation. We recommend full species sampling and inclusion of multiple accessions representing individual species in phylogenies to highlight nonmonophyletic species, which we predict will be frequent in rain forest and savanna, and which represent excellent case studies of incipient speciation. Contents Summary 25 I. Introduction 25 II. Neotropical biomes 26 III. Coalescence 27 IV. Species from seasonally dry tropical forests (SDTFs) 27 V. Species from rain forest, with particular focus on Amazonia 28 VI. Ages of species 32 VII. Species from neotropical savannas 33 VIII. Conclusions and ways forward 34 Acknowledgements 35 References 35